PENERAPAN REHABILITASI DAN PENGOBATAN PASIEN NARKOTIKA DALAM PASAL 53 DAN PASAL 54 UNDANG- UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Krismanko Padang; Yusuf Setyadi (INTELIGENSIA MEDIA, 2022)
Article 54 of Law Number 35 of 2009 stipulates that Narcotics addicts and victims of Narcotics abuse are required to undergo medical rehabilitation and social rehabilitation. This regulation is categorized as a “special” regulation that deviates from the general criminal system prevailing in Indonesia. It is called